2016
DOI: 10.1098/rsfs.2016.0006
|View full text |Cite
|
Sign up to set email alerts
|

Cut marks on bone surfaces: influences on variation in the form of traces of ancient behaviour

Abstract: Although we know that our lineage has been producing sharp-edged tools for over 2.6 Myr, our knowledge of what they were doing with these tools is far less complete. Studies of these sharp-edged stone tools show that they were most probably used as cutting implements. However, the only substantial evidence of this is the presence of cut marks on the bones of animals found in association with stone tools in ancient deposits. Numerous studies have aimed to quantify the frequency and placement of these marks. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…High resolution digital images of the median cross-section of suspected cut marks were captured and the depth, breadth and opening angle were measured using integrated tools. While these measurements are often used to describe the size of cut marks [46, 52, 5759, 63, 64], the depth and breadth of a mark can greatly vary depending on the butchery action, carcass size or hardness of the bone surface [57, 58, 63]. Furthermore, the opening angle of a cut mark varies according to the attrition of the tool edge [59, 64].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…High resolution digital images of the median cross-section of suspected cut marks were captured and the depth, breadth and opening angle were measured using integrated tools. While these measurements are often used to describe the size of cut marks [46, 52, 5759, 63, 64], the depth and breadth of a mark can greatly vary depending on the butchery action, carcass size or hardness of the bone surface [57, 58, 63]. Furthermore, the opening angle of a cut mark varies according to the attrition of the tool edge [59, 64].…”
Section: Methodsmentioning
confidence: 99%
“…While these measurements are often used to describe the size of cut marks [46, 52, 5759, 63, 64], the depth and breadth of a mark can greatly vary depending on the butchery action, carcass size or hardness of the bone surface [57, 58, 63]. Furthermore, the opening angle of a cut mark varies according to the attrition of the tool edge [59, 64]. The breadth ratio (the ratio between the breadth at the top and the breadth at the bottom of the cut mark) [58] better illustrates the shape of the groove (\/ or |_|) and is a good criterion for distinguishing between cut marks made with stone tools and modifications produced by other effectors [4446, 52, 58].…”
Section: Methodsmentioning
confidence: 99%
“…In his raw material ranking system based on replication experiments, Callahan (1979) suggests that flints are easier to work than argillite (see Braun, Plummer, Ferraro, Ditchfield, & Bishop, 2009 for more extensive discussion of stone tool raw material qualities based on physical properties). Although this study does not focus on the effect of raw material on cut mark morphology (e.g., Braun, Pante, & Archer, 2016;Greenfield, 2006;Maté-González et al, 2017), recent studies have found that the hardness of tool edges can affect cut mark morphology (Braun et al, 2016). Turning to the archaeological record, Braun et al (2009) found that hominins at Kanjera South, Kenya, were selecting raw materials to make Oldowan tools based on their durability (the ability of an edge to resist degradation by a static or dynamic force) rather than their fracture predictability (the consistency with which a particular type of stone fractures), and Stout, Quade, Semaw, Rogers, and Levin (2005) found that hominins at Gona preferred finer grained, phenocryst-poor materials for Oldowan toolmaking.…”
Section: Discussionmentioning
confidence: 99%
“…Among those would be cut mark variability according to different types of carcasses, depending on animal size, animal age (regarding the hardness or fragility of cortical bone surfaces), the butcher's physical characteristics (different degrees of strength applied to cut‐marking) and/or the degree of wear‐use of lithics. Some of these variables have recently been tested by Braun et al (), who showed that the hardness of tool edges and the hardness of bones affect cut‐mark morphology. Here, we have documented different mark properties according to the raw material used.…”
Section: Discussionmentioning
confidence: 99%